IMPLEMENTATION OF PAMEKASAN REGENCY RPJMD 2018-2022 FOR MANPOWER SECTOR - Tamam, Baddrut (Airlangga Development Journal, 2024)
Pamekasan Regency has the authority to administer government affairs in the context of regional autonomy in accordance with Law Number 23 of 2014 concerning Regional Government. As stated in the 2018-2023 RPJMD of Pamekasan Regency, what is meant by this priority program are programs that directly touch the public interest, are monumental, cross-functional, large-scale and have high urgency and have a broad impact on the community. One of the priority programs in the field of employment is the New Entrepreneurship. The New Entrepreneurship Program is important because economic management is not yet optimal. Meanwhile, the success of policy implementation can be measured from the process and the achievement of the final results, namely: whether or not the goals to be achieved are achieved. This study will use the theory of George C. Edward III which holds that policy implementation is influenced by four variables: communication, resources, disposition, and bureaucratic structure.